Development of a screening platform to discover natural products active against SARS-CoV-2 infection using lung organoid models - Joo-Eun Lee; Se Yun Jeong; Zijun Li; Hyun-Yi Kim; Hyun-Woo Kim; Min Jeong Yoo; Hee Joo Jang; Do-Kyun Kim; Namki Cho; Hee Min Yoo; Ki Hyun Kim (Biomaterials Research, 2023)
Abstract Background Natural products can serve as one of the alternatives, exhibiting high potential for the treatment and prevention of COVID-19, caused by SARS-CoV-2. Herein, we report a screening platform to test the antiviral efficacy of a natural product library against SARS-CoV-2 and verify their activity using lung organoids. Methods Since SARS-CoV-2 is classified as a risk group 3 pathogen, the drug screening assay must be performed in a biosafety level 3 (BSL-3) laboratory. To circumvent this limitation, pseudotyped viruses (PVs) have been developed as replacements for the live SARS-CoV-2. We developed PVs containing spikes from Delta and Omicron variants of SARS-CoV-2 and improved the infection in an angiotensin-converting enzyme 2 (ACE2)-dependent manner. Human induced pluripotent stem cells (hiPSCs) derived lung organoids were generated to test the SARS-CoV-2 therapeutic efficacy of natural products. Results Flavonoids from our natural product library had strong antiviral activity against the Delta- or Omicron-spike-containing PVs without affecting cell viability. We aimed to develop strategies to discover the dual function of either inhibiting infection at the beginning of the infection cycle or reducing spike stability following SARS-CoV-2 infection. When lung cells are already infected with the virus, the active flavonoids induced the degradation of the spike protein and exerted anti-inflammatory effects. Further experiments confirmed that the active flavonoids had strong antiviral activity in lung organoid models. Conclusion This screening platform will open new paths by providing a promising standard system for discovering novel drug leads against SARS-CoV-2 and help develop promising candidates for clinical investigation as potential therapeutics for COVID-19. Graphical Abstract